Rescaling as a class relationship and process: The case of public procurement law in Turkey - (:unkn) unknown (ELSEVIER SCI LTD, 2006)
In this study we focus on two problematic aspects of the recent rescaling literature: overgeneralization of abstractions rather than examination of concrete class forces; and unidirectional understanding of the relationship between rescaling processes in the core and periphery, where rescaling is seen as an outcome of the uneven development of capitalism based on the tendency of over-accumulated capitals in the core to move to the periphery. We suggest an alternative approach that conceives rescaling as a class relationship and process shaped by the contradictory interaction between global capitals in the core and newly growing capitals in the periphery. Through a study of the formation and transformation of the public procurement law in Turkey (2001-2005), we illustrate that the rescaling of the Turkish public procurement market was not only shaped by global capitals unidirectionally, but through their contradictory interaction with the domestic capitals in Turkey. Although the initial law was formed under the hegemony of global capitals, the AKP government then made many attempts to change the law in line with the demands of domestic capital groups. In this process, scale was shaped by the unequal but mutual power relationships between global and domestic capital groups. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: scale; globalization; capital; state; political economy; Turkey; GEOGRAPHICAL SCALE; GLOBALIZATION; LIMITS; POWER; STATE